Principles of designing information security systems at commercial enterprises ("Journal "U". Economy. Management. Finance.", 2022)
The article describes and classifies the main methods and means of information protection. The issues of protection against unauthorized access to information stored at local automated workplaces, from viruses, Trojans, malware, spyware and other uncontrollable factors are considered. The article provides examples of implementation and describes the shortcomings of systems and methods of information protection.
Keywords: data protection; quality of systems and programs; information technologies; information security systems; information system; local information protection; information system composition; unauthorized access to information; vulnerabilities of information systems; information system project